Kinematics Analysis of Cervical Rotation-Traction Manipulation Measured by a Motion Capture System. (11th October 2017) - Liguo, Zhu; Minshan, Feng; Xunlu, Yin; Shangquan, Wang; Jie, Yu
Abstract : Objectives . To analyze the kinematics of cervical rotation-traction manipulation (CRTM). Methods . An experimental study measuring the kinematics of CRTM was conducted. A total of 18 healthy volunteers participated in the study. A single manipulator operated the CRTM for all subjects. Motion capture technology was adopted to track the trajectory during the CRTM operation. Results . The manipulated side did not influence the cervical spine motion. The motion ranges obtained during CRTM were well below the active range of motion reported in the literature. The head rotation angle after thrusting was less than the angle of the rotary-position (P < 0 . 05 ). There was no significant difference in the head rotation angle between pretraction and upward-thrust. The thrust direction of CRTM was mainly upward. The thrust operation was of high-velocity and low-amplitude (thrust velocity: 203.06 ± 49.95  mm/s; thrust acceleration: 3836.27 ± 1262.28  mm/s 2 ; thrust displacement: 3.25 ± 1.30  mm). Conclusions . CRTM has clear operation steps and repeatability that is suitable for clinical application.